Education and South Korea’s New Southern Policy: Locus and Prospects - Inero Ancho; Kyungeun Kim; Saehoon Park (Universitas Muhammadiyah Yogyakarta, 2021)
The implementation of South Korea's Southern Policy (NSP) has undoubtedly resulted in significant changes to the region's economic and political landscape. NSP may be viewed as a basis for Korea and a Southeast Asian nation to foster